Growth, yield and fiber quality characteristics of Bt and non-Bt cotton cultivars in response to boron nutrition - Muhammad MEHRAN; Muhammad ASHRAF; Sher Muhammad SHAHZAD; Muhammad Siddique SHAKIR; Muhammad Tehseen AZHAR; Fiaz AHMAD; Alamgir ALVI (Journal of Cotton Research, 2023)
Abstract Background Boron (B) deficiency is an important factor for poor seed cotton yield and fiber quality. However, it is often missing in the plant nutrition program, particularly in developing countries. The current study investigated B's effect on growth, yield, and fiber quality of Bt (CIM-663) and non-Bt (Cyto-124) cotton cultivars. The experimental plan consisted of twelve treatments: Control (CK); B at 1 mg·kg−1 soil application (SB1); 2 mg·kg−1 B (SB2); 3 mg·kg−1 B (SB3); 0.2% B foliar spray (FB1); 0.4% B foliar spray (FB2); 1 mg·kg−1 B + 0.2% B foliar spray (SB1 + FB1); 1 mg·kg−1 B + 0.4% B foliar spray (SB1 + FB2); 2 mg·kg−1 B + 0.2% B foliar spray (SB2 + FB1); 2 mg·kg−1 B + 0.4% B foliar spray (SB2 + FB2); 3 mg·kg−1 B + 0.2% B foliar spray (SB3 + FB1); 3 mg·kg−1 B + 0.4% B foliar spray (SB3 + FB2). Each treatment has three replications, one pot having two plants per replication. Results B nutrition at all levels and methods of application significantly (P ≤ 0.05) affected the growth, physiological, yield, and fiber quality characteristics of both cotton cultivars. However, SB2 either alone or in combination with foliar spray showed superiority over others, particularly in the non-Bt cultivar which responded better to B nutrition. Maximum improvement in monopodial branches (345%), sympodial branches (143%), chlorophyll-a (177%), chlorophyll-b (194%), photosynthesis (169%), and ginning out turn (579%) in the non-Bt cultivar was found with SB2 compared with CK. In Bt cultivar, although no consistent trend was found but integrated use of SB3 with foliar spray performed relatively better for improving cotton growth compared with other treatments. Fiber quality characteristics in both cultivars were improved markedly but variably with different B treatments. Conclusion B nutrition with SB2 either alone or in combination with foliar spray was found optimum for improving cotton's growth and yield characteristics.